Who governs? Blank spots and blind spots in state boards of education in the United States - VanGronigen, Bryan A.; Young, Michelle D.; Rodriguez, Kevin (Education Policy Analysis Archives, 2022)
State boards of education (SBOEs) are one of many governmental entities that reside within the larger educational policymaking sphere. With recent U.S. federal legislation devolving more authority over education to states, state-level governmental entities like SBOEs are in the spotlight perhaps now more than ever. Yet not much has been published about SBOE structures and functions, much less about their members and how they might influence educational policies and education broadly. Using critical policy analysis methods, this descriptive study focused on two areas: (a) the criteria and processes that states use to select SBOE members, and (b) the characteristics of today’s SBOE members (e.g., demographics) and the extent to which SBOEs are representative portraits of the states they serve. Findings report similarities and differences among members within and between the 47 U.S. states with SBOEs. We close by critically assessing our findings, especially whether SBOE member selection criteria and processes and SBOE members themselves are well-positioned to best represent their constituents.